(untitled) (IJM: Journal of Multidisiplinary, 2025)
Sepsis is one of the leading causes of neonatal death in developing countries, requiring intensive care for neonates with neonatal sepsis. Neonatal sepsis is often accompanied by respiratory issues such as ineffective airway, which requires positional care such as the quarter prone position. The quarter prone position is a position that can enhance the effectiveness of secretions removal. The research design is a case study, including assessment, diagnosis, intervention, implementation, and evaluation. The main intervention is the application of the quarter prone position to enhance secretions removal and support respiratory function. In this case, nursing problems arose, such as spontaneous ventilation impairment, ineffective airway clearance, nutritional deficit, ineffective thermoregulation, ineffective renal perfusion risk, and risk of shock. After evaluating nursing care over 4 days of treatment, the unresolved issues were spontaneous ventilation impairment, ineffective airway clearance, nutritional deficit, ineffective thermoregulation, and ineffective renal perfusion risk, while the risk of shock was partially resolved. Further interventions and monitoring are required. It is recommended that healthcare professionals adopt positional changes like the quarter prone to improve lung ventilation and reduce respiratory issues in neonates.